Grassing as potential factor in Gastrointestinal Nematodiasis in Goat in Banyumas District - Indradji, M; Yuwono, Endro (ANIMAL PRODUCTION, 2004)
Goat system manajemen like housing, feeding dan grassing have been studied on the diseases association in gastrointestinal nematodiasis infection. The method applied was survey on 150 goat (Jawarandhu) faeces sample in Banyumas District. The Research was carried out from July to September 2004. The result showed thatÂ  the nematode infection 1,54 times to goat if grassing and 88,62% infection in groups. Housing, Feeding have no risk and associated with disease infection. (Animal Production 6(2): 95-100 (2004)Â Key words : management system, disease association, nematode